2017
DOI: 10.1038/s41598-017-03932-1
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus activates cGAS through the release of mitochondrial DNA

Abstract: Cyclic GMP-AMP synthetase (cGAS) is a DNA-specific cytosolic sensor, which detects and initiates host defense responses against microbial DNA. It is thus curious that a recent study identified cGAS as playing important roles in inhibiting positive-sense single-stranded RNA (+ssRNA) viral infection, especially since RNA is not known to activate cGAS. Using a dengue virus serotype 2 (DENV-2) vaccine strain (PDK53), we show that infection creates an endogenous source of cytosolic DNA in infected cells through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(157 citation statements)
references
References 41 publications
(55 reference statements)
4
141
0
Order By: Relevance
“…S5D, S5E). A number of recent studies have demonstrated that cytosolic release of mtDNA can activate the cGAS/STING DNA sensing pathway that triggers the production of type I IFNs (Rongvaux et al, 2014; West et al, 2015; White et al, 2014; Aguirre et al, 2017; Sun et al, 2017). Therefore we asked whether cholesterol treatment of BMDMs would show evidence of type I IFN induction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5D, S5E). A number of recent studies have demonstrated that cytosolic release of mtDNA can activate the cGAS/STING DNA sensing pathway that triggers the production of type I IFNs (Rongvaux et al, 2014; West et al, 2015; White et al, 2014; Aguirre et al, 2017; Sun et al, 2017). Therefore we asked whether cholesterol treatment of BMDMs would show evidence of type I IFN induction.…”
Section: Resultsmentioning
confidence: 99%
“…However, the AIM2 HIN-200 domain is not sequence-specific, and therefore host DNA represents a potential pool of ligand if the nucleic acid is de-compartmentalized. Cytosolic release of mtDNA can trigger the cGAS-dependent DNA sensing pathway in the context of caspase-3/7- and TFAM-deficiency (Rongvaux et al, 2014; West et al, 2015; White et al, 2014) and in dengue virus infected cells (Aguirre et al, 2017; Sun et al, 2017), but there are few examples of AIM2 activation by mtDNA. A number of studies have suggested that oxidized mtDNA can act as a ligand for NLRP3 (Nakahira et al, 2011; Shimada et al, 2012), which is consistent with our findings that NLRP3 redundantly contributes to cholesterol-dependent IL-1β production.…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine adjuvant chitosan also produces cGAS and STING-dependent IFN-I responses through mitochondrial stress and cytosolic mtDNA accumulation [21 • ]. Notably, mtDNA leakage occurs during natural herpes simplex virus infection [20 • ], and recent studies also point to mtDNA as an innate sensor for the RNA-encoding virus Dengue [22,23]. As a strategy for evading innate immune detection by the host, the viral protease cofactor NS2B degrades cGAS [22], which is activated during the course of Dengue infection by mitochondrial damage and mtDNA leakage [22,23].…”
Section: Dna Sensing During Infectionsmentioning
confidence: 99%
“…Notably, mtDNA leakage occurs during natural herpes simplex virus infection [20 • ], and recent studies also point to mtDNA as an innate sensor for the RNA-encoding virus Dengue [22,23]. As a strategy for evading innate immune detection by the host, the viral protease cofactor NS2B degrades cGAS [22], which is activated during the course of Dengue infection by mitochondrial damage and mtDNA leakage [22,23]. cGAMP molecules can traffic to adjacent cells via gap junctions [24 •• ], and the mtDNA-dependent innate immune response to Dengue is important for limiting spread of the infection to neighboring cells [23].…”
Section: Dna Sensing During Infectionsmentioning
confidence: 99%
See 1 more Smart Citation